Contribution of Small Pockets of Forests towards Carbon Sequestration - TFRI Jabalpur, A Case Study - verma, Sangeeta; Jain, Avinash (Indian Forester, 2020)
This study was conducted to quantify the contribution of the plantations and natural forests in Tropical Forest Research Institute (TFRI) Jabalpur campus towards carbon sequestration. The standing carbon stock and annual sequestration for the years 2015, 2016 and 2017 were calculated in natural vegetation and plantations present in TFRI premises. A total of 42 quadrats of 10m Ã— 10m area were laid out in the study area in which a total of 436 individuals of trees belonging to 28 different species were present. The carbon stock in plantations and natural forest was calculated to be 75.31 t/ha and 76.34 t/ha respectively during 2015, which enhanced to 79.99 t/ha and 82.17 t/ha in 2016 and 82.37 t/ha and 85.49t/ha in 2017. Carbon sequestered by trees in plantations was found to be more than natural forest annually. Keeping in view the global concern towards carbon sequestration and its mitigating role in climate change, present study was undertaken to assess carbon stocks and annual sequestration in the tree plantations raised in the TFRI campus.